2015
DOI: 10.1055/s-0035-1563712
|View full text |Cite
|
Sign up to set email alerts
|

Newborns Referred for Therapeutic Hypothermia: Association between Initial Degree of Encephalopathy and Severity of Brain Injury (What About the Newborns with Mild Encephalopathy on Admission?)

Abstract: Our results demonstrated that several newborns with an initial mild encephalopathy developed subsequent brain injury, especially when they were not cooled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 27 publications
6
40
1
Order By: Relevance
“…7 Additionally in a recent cohort study, Gange-Loranger et al reported that among 13 infants with mild NE who underwent TH, 31% (4/13) had MRI changes consistent with HI injury. 26 The rate of both any MRI abnormality, and MRI hypoxic-ischemic injury, among those with mild NE in these studies is consistent with our own findings. However none of these studies provided sufficient details regarding the pattern or severity of MRI cerebral injuries to allow further meaningful comparison across studies.…”
Section: Discussionsupporting
confidence: 91%
“…7 Additionally in a recent cohort study, Gange-Loranger et al reported that among 13 infants with mild NE who underwent TH, 31% (4/13) had MRI changes consistent with HI injury. 26 The rate of both any MRI abnormality, and MRI hypoxic-ischemic injury, among those with mild NE in these studies is consistent with our own findings. However none of these studies provided sufficient details regarding the pattern or severity of MRI cerebral injuries to allow further meaningful comparison across studies.…”
Section: Discussionsupporting
confidence: 91%
“…Limitations of PRIME are the long period required for enrollment, absence of follow-up aEEG at different time points or continuously, absence of all outcome measures on some infants, and the relative center imbalance in patient enrollment (Supplemental material -Appendix). During study design there were limited data on short-term outcomes of mild NE infants 6,7 and systematic data on long-term outcomes (from the pre-hypothermia era) was favorable 4,5 . Thus, a low frequency of short-term abnormalities was expected and our primary objective was to determine if mild NE diagnosed at < 6h of age was associated with short-term neurological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…2 Infants in whom the worst level of encephalopathy during hospitalization was mild had few if any adverse outcomes. [2][3][4][5] Recently, studies have suggested that some infants with perinatal acidosis and mild NE diagnosed at < 6h of age have neurological abnormalities at discharge from the neonatal intensive care unit (NICU) 6 , cerebral findings of hypoxic-ischemic injury on brain magnetic resonance imaging (MRI) 7 , or high rates of disability at 5 years of age. 8 However, a prospective and systematic evaluation of the frequency of neurological abnormalities of these mild NE infants is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A moderate degree of injury (30-60% tissue loss) is required to see a neuroprotective effect of HT in this model [31,53] . Whether mild injury should be eligible for cooling in neonates is still debated, as the neuroprotective effect of HT has not been clarified for these patients [54] . Rat pups are highly variable in how much hypoxia they can withstand before cellular death is seen, and the same is likely to be the case for human neonates.…”
Section: Discussionmentioning
confidence: 99%